A novel porous silica monolith functionalized with 5-amino-1, 10-phenanthroline for SPE of metal ions in groundwater samples prior to their analysis using ICP-MS. Issue 20 (4th May 2018) - AlSuhaimi, Awadh O.; AlMohaimadi, Khaled M.; AlAlawi, Bader N.; Ali, Imran
Abstract : This work reports a facile and inexpensive preparation of porous silica monoliths via an in situ sol–gel method using potassium silicate precursors in the presence of porosity controlling and drying regulatory additives. Abstract : Porous silica monoliths are being used for favorable applications in separation science due to their inherent characteristics such as their rigid skeleton, large surface area, affordable starting materials and straightforward sol–gel synthesis under ambient conditions. This work reports a facile and inexpensive preparation of porous silica monoliths via an in situ sol–gel method using potassium silicate precursors in the presence of porosity controlling and drying regulatory additives that were polymerized inside 2.5 cm long and 7.5 mm i.d. soda-lime glass syringes. The monolithic materials were chemically functionalized with 5-amino-1, 10-phenanthroline (5-aphen) and characterized using SEM, FTIR, TGA and elemental analysis. The monolith exhibited excellent chelating properties with fast adsorption capacities of 0.132, 0.139, 0.140 and 0.142 mM g −1 for Zn, Co, Ni and Cu, respectively. The chelator was applied successfully as a solid phase sorbent for the sample preparation of transition metals in groundwater samples. The method accuracy was confirmed via the extraction of Cu, Co, Ni, and Zn metal ions from a groundwater certified reference material CRM SLRS-4 sample prior to ICP-MS analysis. The results were comparable with the certified values for the analyzed metal ions. The method showed efficient performance when applied for the SPE of the reported metal ions in groundwater samples from Al-Madinah Al-Munawarah city, Kingdom of Saudi Arabia. The developed SPE sorbent is effective and useful for the pre-concentration of the reported metal ions in any body of water.